Hakekat Belajar dan Peranan Edutaiment Dalam Bingkai Pendidikan Islam - Muh. Sya’rani (STKIP Pesisir Selatan, 2024)
An educator can only carry out his duties well if he obtains clear and correct answers through understanding the basic elements and concepts of education as a whole, including the nature of learning as one of the most urgent elements in the world of education. The research method uses Library Research (Library Study). In Islam, the essence of learning is at least seen as first; learning is a theo-anthropocentric necessity. Second; learning is an activity that can be done anytime and anywhere and third; that learning can not only be done by oneself, but also with the help of others, both in the form of asking questions and so on, and fourth: that the learning process can be designed or engineered in various forms and methods carried out by oneself and others in achieve these learning objectives, so that the results achieved can be better. Even though the edutainment method is believed to be a learning method that developed in the western world, essentially Islam, through the Koran and Hadith, has laid the foundation for enjoyable learning as the jargon of this edutainment method. This certainly shows that in Islam, especially the Koran which is humanity's guide, it is not only understood normatively as a text that regulates Sharia laws.